Designing of two mixed variable lot-size sampling plans using repetitive sampling and resampling based on the process capability index. Issue 4 (1st October 2016) - Balamurali, Saminathan; Aslam, Muhammad; Jun, Chi-Hyuck
ABSTRACT: In this article, we propose two types mixed variable lot-size sampling plans using the process capability index. The first one is the mixed variable lot-size repetitive sampling plan and the other is the mixed variable lot-size sampling plan for resubmitted lots. The design methodology of the proposed mixed sampling plans for symmetric and asymmetric fraction nonconforming cases is presented. Tables are constructed to determine the optimal parameters for practical applications. The industrial applications of the proposed mixed sampling plans are explained with illustrative examples. Comparison of the proposed sampling plans with other existing sampling plans is also made.